2019
DOI: 10.1177/0300060519867168
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre survey of pain management in cancer patients and physicians attending radiotherapy clinics in Shandong Province, China

Abstract: Objective To obtain a better understanding of the prevalence and management of pain in patients undergoing radiotherapy for cancer in Shandong Province, China. Methods This cross-sectional study used a questionnaire during face-to-face interviews to collect data from physicians and patients regarding the recognition, prevalence and treatment of pain during the waiting period before commencement of radiotherapy and during the radiotherapy period. Physicians and patients were recruited from 10 tertiary Class A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These were similar to those reported in previous studies in China. 25 , 26 , 28 , 29 This indicated that the WHO and NCCN guidelines for cancer pain are widely used in China and considered as the primary references for the treatment of cancer pain. In China, many efforts have been taken to improve pain management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These were similar to those reported in previous studies in China. 25 , 26 , 28 , 29 This indicated that the WHO and NCCN guidelines for cancer pain are widely used in China and considered as the primary references for the treatment of cancer pain. In China, many efforts have been taken to improve pain management.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the findings from previous studies. 22 , 25 , 26 This suggested a gap between existing treatment guidelines and real-world clinical practice. Thus, hospitals should provide timely and continuous education and training for updated guidelines to the medical staff, particularly for opioid dose calculation and conversion from oral to parenteral routes of administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations